Kinetic and Equilibrium Studies of Removal of Pb(II) and Cd(II) Ions from Aqueous Solution by Modified Duolite XAD-761 Resins - THARANITHARAN, V.; SRINIVASAN, K. (Asian Journal of Chemistry, 2010)
Complete mixing of phenol-formaldehyde polymeric resin (Duolite XAD-761) with anionic surfactant-sodium dioctyl sulphosuccinate (SDOSS) and EDTA-disodium salt (chelating agent) in an aqueous solution led to the formation of a modified resin for the removal of Pb(II) and Cd(II) ions from aqueous solution. The effect of experimental parameters such as pH, contact time and modified resin dosage on the Pb(II) and Cd(II) ions removal was studied. The obtained data were fitted with the Langmuir and Freundlich equations to describe the equilibrium isotherms. The kinetic data were fitted with the pseudo-first-order and pseudo-second-order models. It was found that pH played a major role in the adsorption process. The maximum adsorption capacity for Pb(II) and Cd(II) on modified resin calculated from Langmuir isotherm was found to be 46.66 and 59.52 mg g-1, respectively. The optimum pH range for the removal of Pb(II) and Cd(II) was found to be 4-7 and 4-8, respectively. Langmuir isotherm model was found to best describe the experimental data [R2 ≥ 0.999 for Pb(II) and R2 ≥ 0.954 for Cd(II)]. The kinetic rates were best fitted to the pseudo-second-order model [R2 ≥ 0.999 for Pb(II) and R2 = 1 for Cd(II)]. Thermodynamic study showed the adsorption was a spontaneous process. The metal ions could be successfully recovered from the modified resin by treatment with 7-8 % NaCl. The modified resins thus regenerated could be used again to remove the heavy metal ions. Based on all results, it can also be concluded that it can be evaluated as an alternative adsorbent for removing Pb(II) and Cd(II) from aqueous solution.